Solving the taxonomic identity of Hipposideros cineraceus sensu lato (Chiroptera: Hipposideridae) in the Thai-Malay Peninsula, with the description of a new species - PHUTITA, WONGWAIYUT; SUNATE, KARAPAN; PUCHIT, SAEKONG; CHARLES M., FRANCIS; ANTONIO, GUILLÉN-SERVENT; Juliana, Senawi; Faisal Ali, Anwarali Khan; PAUL J., J. BATES; SOPARK, JANTARIT; PIPAT, SOISOOK (Magnolia Press, 2023)
A new species of small Hipposideros in the bicolor group is described based on specimens from Thailand and Malaysia. It can be distinguished from other small Hipposideros in Southeast Asia by a combination of external, craniodental, and bacular morphology, as well as echolocation call frequency. The new species has a distinct rounded swelling on the internarial septum of the noseleaf, with a forearm length of 35.3–42.6 mm, greatest skull length of 15.94–17.90 mm, and a call frequency of maximum energy of 132.3–144.0 kHz. Although clearly different in morphology, the new species forms a sister clade with H. kunzi and H. bicolor in the phylogenetic trees based on mitochondrial DNA. In addition, this study reports echolocation and genetic data, with a confirmed record of H. einnaythu from Thailand for the first time. The new species most closely resembles H. einnaythu. However, it differs in the details of the noseleaf and craniodental morphology, and it has a genetic distance of 9.6% and 10.4% based on mitochondrial COI and ND2, respectively. It is currently documented from five localities: two in peninsular Thailand, at Hala Forest in Yala Province, and Phru To Daeng Swamp Forest in Narathiwat Province, one from peninsular Malaysia at Krau Wildlife Reserve in Pahang, and another two in Sabah, Malaysian Borneo at Gunung Kinabalu, and near Madai Caves. However, it is likely that many previous records of “H. cineraceus” from Borneo refer to this species. Most records of the species are from lowland evergreen rainforest, though one record from Sabah was at 1800m. The roosting sites for this new species are currently unknown. Future research with a combination of data such as genetics, echolocation and morphology would be necessary to further determine the species geographic distribution in Southeast Asia.